Dominant tolerance and linked suppression induced by therapeutic antibodies do not depend on Fas-FasL interactions. - Honey, K; Cobbold, S; Waldmann, H (2000)
BACKGROUND: Nonlytic anti-CD4 monoclonal antibody therapy can be used to induce transplantation tolerance in rodent models. Such tolerance is often associated with dominant regulation, mediated by CD4+ cells, and characterized by infectious tolerance and linked suppression. Understanding the mechanisms by which CD4+ regulatory cells function may improve the manner in which current immunosuppressants are applied and may lead to the development of new tolerance-inducing therapeutics. Fas-mediated apoptosis has been characterized as an important mechanism of peripheral self-tolerance and we here examine whether it has any role in anti-CD4 monoclonal antibody-induced dominant tolerance. METHODS: Tolerance to transplanted skin and bone marrow, mismatched for multiple minor histocompatibility antigens, was induced in Fas mutant and control mice using anti-CD4 and anti-CD8 monoclonal antibodies. To test for linked suppression, animals were transplanted with a second graft-bearing tolerated and third party antigens. The ability of splenocytes from tolerant animals to suppress graft rejection was assessed by transfer into partially immunocompromised recipients. RESULTS: Monoclonal antibody therapy rendered Fas mutant mice tolerant of minor disparate skin and bone marrow. Splenocytes from these and control tolerant animals when transferred into partially immunocompromised Fas mutant or control recipients, induced antigen-specific suppression of graft rejection. Additionally, tolerant Fas mutant mice accepted grafts bearing tolerated and third party antigens. CONCLUSIONS: Signal transduction through the Fas receptor plays no essential role in the induction of tolerance using anti-CD4 and anti-CD8 monoclonal antibodies or its maintenance by active regulation.